Introduction to nonlinear optimization: Theory, algorithms, and applications with python and matlab - Beck, Amir (Philadelphia Mathematical Optimization Society, 2023)
Built on the framework of the successful first edition, this book serves as a modern introduction to the field of optimization. The author$1 (Bs objective is to provide the foundations of theory and algorithms of nonlinear optimization as well as to present a variety of applications from diverse areas of applied sciences. Introduction to Nonlinear Optimization gradually yet rigorously builds connections between theory, algorithms, applications, and actual implementation. s